2014
DOI: 10.1007/s00299-014-1722-4
|View full text |Cite
|
Sign up to set email alerts
|

Biotechnology of oil palm: strategies towards manipulation of lipid content and composition

Abstract: Oil palm is a major economic crop for Malaysia. The major challenges faced by the industry are labor shortage, availability of arable land and unstable commodity price. This has caused the industry to diversify its applications into higher value products besides increasing its yield. While conventional breeding has its limitations, biotechnology was identified as one of the tools for overcoming the above challenges. Research on biotechnology of oil palm began more than two decades ago leveraging a multidiscipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
45
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 42 publications
1
45
0
1
Order By: Relevance
“…Commercially refined palm oil from fruit mesocarp contains predominantly palmitic acid (44%), oleic acid (39%) and stearic acid (5%) (Dauqan et al, 2011;Sundram et al, 2003;Sundram, 2000). Genetic engineering has been used to generate transgenic oil palms containing more high-value fatty acids to boost sustainability (Parveez et al, 2015). Biochemical studies of lipid biosynthetic pathway revealed significant flux control in the fatty acid biosynthesis over lipid assembly and the results also suggested that manipulation of a single enzyme step would…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Commercially refined palm oil from fruit mesocarp contains predominantly palmitic acid (44%), oleic acid (39%) and stearic acid (5%) (Dauqan et al, 2011;Sundram et al, 2003;Sundram, 2000). Genetic engineering has been used to generate transgenic oil palms containing more high-value fatty acids to boost sustainability (Parveez et al, 2015). Biochemical studies of lipid biosynthetic pathway revealed significant flux control in the fatty acid biosynthesis over lipid assembly and the results also suggested that manipulation of a single enzyme step would…”
Section: Introductionmentioning
confidence: 96%
“…is a highly valuable economic crop in Malaysia and is the world's highest yielding oil-bearing crop (Parveez et al, 2015;Singh et al, 2013b). Malaysian plantations produce 3.5 t of versatile and nutritious palm oil per hectare annually (Kirkland, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This requires the palm oil industry to tackle the challenges in meeting the growing worldwide demand for palm oil as food, biodiesel and industrial non-food uses, such as oleochemicals. Improvement of oil palm crop by genetic engineering could have an important role to play in fulfilling the growing global need for oils and fats (Parveez et al, 2015a). Methods for the genetic engineering of oil palm will have to be developed in order to face future challenges.…”
Section: Introductionmentioning
confidence: 99%
“…Effective selection is an absolute requirement for successful transformation and regeneration of stable transgenic oil palm (Parveez et al, 2015a). Selection process requires suitable selection agents such as herbicide and antibiotic supplemented in selection media, allowing transformed cells to grow without any deleterious effects.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there is a compendium of literature sources that describe the basis for lipid composition of relevant mutants. Both Parveez et al (2014) and Goold et al (2014) review cover storage and neutral lipids in oil palm and microalgae, respectively. Parveez et al describe advances in biotechnology of oil palm that includes biochemical studies, gene and promoter isolation, vector construction for transformation, and genetic transformation technology.…”
mentioning
confidence: 99%